Optimizing Pregnancy Outcomes: The Importance of Pre-Marital and Preconception Care - Mulyaningsih, Erika Agung; Novi Anggraeni; Amirul Amalia (CV. Media Digital Publikasi Indonesia, 2024)
Premarital and preconception care are essential components in improving maternal and newborn health outcomes. This community service aims to evaluate the importance of premarital and preconception counseling, with a focus on its role in reducing the risks associated with unplanned pregnancy, complications during pregnancy, and adverse neonatal outcomes. Although the benefits of premarital and preconception care are clear, access and awareness are still limited in Indonesia, especially among couples planning to marry. This community service was carried out through a national webinar attended by midwifery students, midwives and midwifery/health lecturers. The number of participants was 815 people. Based on the questionnaire that we gave to the midwives, only a few received preconception visits even though the implementation of premarital and preconception care can significantly improve reproductive health outcomes, reduce maternal and infant mortality, and help prospective couples plan a healthy pregnancy. The results of this activity identified barriers to accessing these services, including lack of awareness and education. The hope from this activity is that midwives can expand health education programs aimed at increasing community awareness of the benefits of premarital and preconception care in creating healthier family planning outcomes